(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
It is possible to prevent the growth of traffic accidents by analyzing the system of training drivers of motor vehicles in developed foreign countries and by applying the best practices collected by them. The article presents an analysis of the methods and methodologies used in the system of training motor transport drivers in some developed foreign countries - France, Germany, South Korea and Japan.